Assessment of Bangladeshi rice landraces for drought tolerance under controlled environment (Bangladesh Rice Journal, 2023)
Drought is one of the major challenging abiotic stresses for rice production in Bangladesh. This study investigated 48 rice landraces obtained from different Eco-zones of Bangladesh for their drought tolerance characteristics. Significant variation was observed in morpho-physiological traits such as length of root and shoot, dry weight of root and shoot, leaf stomatal resistance and stomata number. Stomatal conductance, root length, root dry weight showed significant correlation with visual drought score. A cluster analysis based on morpho-physiological characteristics identified six cluster groups and most of the promising drought tolerance landraces were found in cluster VI. Five landraces - Dhapa, Dud Kalam, Dular, Hogla Pata and Keora showed key desired characteristics for dry weight, stomatal conductance, evapotranspiration, water use efficiency and root parameters for drought tolerance. These landraces could be potential sources in breeding program for the development of drought tolerant rice varieties.Bangladesh Rice J. 26 (1): 1-16, 2022